The effect of a training program based on the theory of planned behavior on the self-care of patients with cerebrovascular accident: A randomized controlled trial - Zahra Salajegheh; Behnaz Bagherian; Roghayeh Mehdipour Rabori; Sakineh Sabzevari (Wolters Kluwer Medknow Publications, 2024)
Background: Cerebrovascular accident dramatically impacts patients' lives. However, this chronic disease could be managed by boosting self-care and following healthy behaviors. Accordingly, this trial sought to specify the impact of a training program established on the theory of planned behavior on the self-care of clients with this condition. Materials and Methods: This trial was performed on 80 clients, who were selected using a random numbers table and divided into two equal groups to receive either usual care alone or usual care plus a training program based on the theory of planned behavior (five in-hospital individual sessions for 5 weeks and weekly phone follow-ups for 2 months after discharge). Self-care and the dimensions of the theory of planned behavior were investigated at baseline and 2 months after the last in-hospital session using the standardized Shah version of the modified Barthel index and a researcher-made questionnaire, respectively. Results: The mean score of self-care was significantly higher in the experimental arm at the posttest (Mann-Whitney = 506.00, p = 0.005). Also, the increase in mean change of self-care from baseline to posttest was significantly more in the experimental arm (t78= -6.6, p < 0.001). Such findings were also found for all dimensions of the theory of planned behavior. Conclusions: Based on results, nurses and health policymakers can incorporate training based on the theory of planned behavior into routine care programs for patients with cerebrovascular accident to boost their self-care. The implemented intervention also could be reproduced in other contexts. Hence, further trials are requested to specify the sustainability of the findings.